2003
DOI: 10.1007/s00147-003-0588-0
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid against reperfusion injury in human renal transplantation

Abstract: The cadaveric renal graft is exposed to ischaemic injury during preservation and to oxidative damage during reperfusion. Both these mechanisms are known to cause cell damage, which may impair graft function. Reperfusion injury (RPI) is mediated by reactive oxygen species (ROS). Ascorbic acid (AA) is a potent physiological extracellular scavenger of ROS. We perfused 31 renal grafts immediately before implantation with a solution of Euro-Collins containing 0.5 mg/ml of AA to diminish RPI. From every donor, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Hemodialysis patients exhibit reduced systemic concentrations of VitC and VitC diminishes reperfusion injury in patients undergoing renal transplantation [36,37]. Based on microsomal VitC-dependent EET formation, and the vasodilator properties of EETs in the kidney, we investigated the role of EETs in rat isolated perfused kidneys challenged with bolus doses of VitC (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemodialysis patients exhibit reduced systemic concentrations of VitC and VitC diminishes reperfusion injury in patients undergoing renal transplantation [36,37]. Based on microsomal VitC-dependent EET formation, and the vasodilator properties of EETs in the kidney, we investigated the role of EETs in rat isolated perfused kidneys challenged with bolus doses of VitC (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Although individual EET isomers could not be quantitated by GC/MS analysis, increases in 14,15- trans -EET associated with the inhibition of sEH should play a major role based on the preferred hydrolysis of 14,15- trans -EET by sEH and its potent vasodilator activity in rat renal arcuate arteries [10]. Vasodilator and natriuretic actions of EETs likely contributed to the effects of VitC in the kidney and could provide a direct explanation for the renal protective effects of VitC in reperfusion injuries in renal transplantation [36,37]. Inhibition of EET hydrolysis in the spontaneously hypertensive rat has increased plasma trans -EETs and reduced blood pressure [10].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C is a water-soluble vitamin that mainly occurs in fruits and vegetables [91]. Despite acting in a hydrophilic environment, vitamin C can also impact hydrophobic compartments as it acts synergistically with lipophilic vitamin E [250]. Vitamin C possesses direct as well as indirect antioxidative effects.…”
Section: Vitamin Cmentioning
confidence: 99%
“…The treatment group showed a non-significant trend towards amelioration of inflammation and oxidative stress. In a second study by Norio et al [250] renal cadaveric grafts were treated with 500 mg vitamin C prior to implantation. The authors observed similar results, as the treatment neither affected the incidence on delayed graft function, the rejection rate nor the graft function per se.…”
Section: Kidneymentioning
confidence: 99%
See 1 more Smart Citation